The Impact of Training and Human Resource Development on Healthcare Workers' Performance - Taufik Hermansyah; Iwan Saputra; Lati Sari Dewi; Siti Amirah Makarim (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study examines the effect of training and human resource development on healthcare workers' performance. The research is motivated by the importance of improving the quality of healthcare services through the enhancement of workforce competence and performance. The objectives of this study are to analyze the implementation of training programs, evaluate human resource development practices, assess healthcare workers' performance, and determine the influence of training and human resource development on healthcare workers' performance. This study employed a quantitative descriptive approach with a replicative research design. Primary data were collected through questionnaires using a Likert-scale measurement instrument. The sample consisted of 87 healthcare workers. Data were analyzed using multiple linear regression analysis. The findings indicate that training programs are implemented effectively, human resource development practices are conducted satisfactorily, and healthcare workers' performance is generally at a good level. Furthermore, the results show that training and human resource development have a positive and significant effect on healthcare workers' performance.